Model Tutor Sebaya Dalam Pembelajaran Al-Qur'an Di SMP Negeri 1 Sambi Boyolali Tahun Pelajaran 2015/2016 - Mulyani, Mulyani, Dr. Mohamad Ali, S.Ag, M.Pd (2016)
Al-Qur‟an is the perfect holy scripture with functions as lesson for human being, as the way of life for every muslim to believe, study, read, contemplate, and to be a foundation of law. Model, strategy and good application are needed in learning of Al-Qur‟an. SMP Negeri 1 Sambi Boyolali District has been applying special strategy inthe Al-Qur‟an learning, namely by using peer tutor model. Based on the background, researcher was interested to study further the model of Al-Qur‟an learning in SMP Negeri 1 Sambi Boyolali. Problem statements of the research are: 1) How is the implementation of peer tutor model in the learning of Al-Qur‟an in SMP Negeri 1 Sambi Boyolali in 2015/2016 academic year?. 2) What supporting factors and inhibiting factors are found in the implementation of the peer tutor model in the secondary school? Purposes of the research is to describe the implementation of peer tutor model in learning of Al-Qur‟an in SMP Negeri 1 Sambi Boyolali in 2015/2016 academic year. The research can be useful as a scientific discourse, especially on peer tutor model in learning of Al-Qur‟an. The research is field one with its data are obtained from teachers of Islamic Religious Education, extracurricular counselor of Al-Qur‟an reading and writing, students of 7th and 8th grades, and documents of SMP Negeri 1 Sambi, Boyolali. The data was collected by using interview, observation and documentation. The data was analyzed by using descriptive-qualitative analysis approach. Based on the research and data analysis, it can be concluded the peer tutor model in the secondary school was implemented 2 times a week, 15 minutes before Islamic Religious Education lesson started and also, it was implemented in extracurricular of Al-Qur‟an reading and writing after school hours. The implementation of the learning activity uses halaqah system, namely dividing a class into several small groups and every group has one peer tutor. The peer tutor model has benefits, namely relationship in the learning was closer and friendly and there was no clumsy feeling in asking something, because it was a friendly relationship. However, the peer tutor model can potentially be a noisy and uncontrolled situation. Supporting factor of the model was derived from school and students‟ enthusiasm to be able to read Al-Qur‟an quickly, whereas inhibiting factors consisted of limited time and minimum infrastructure and facility of the learning. Keywords : Model, Peer Tutor, Learning of Al-Qur'an